The Influence of Nutritional Status on Brain Development: Benefits of Exclusive Breastfeeding - Ellen Schavarski Chade; Odonis Rocha Júnior; Nathalia Marçallo Peixoto Souza; Aline Jacoski de Oliveira Krüger da Silva; Luana Mota Ferreira; Jéssica Brandão Reolon; Juliana Sartori Bonini; Fabiane Gomes de Moraes Rego; Marcel Henrique Marcondes Sari (MDPI AG, 2024)
Background: This study aimed to conduct a narrative review approaching the effects of exclusive breastfeeding on neuropsychomotor development. The goal was to provide evidence-based knowledge to inform healthcare practices and policies and promote optimized infant feeding strategies. Methods: Our study reviewed the relevant literature from May and June 2024, covering the publication period between 2013 and 2024. The PubMed database was utilized and searched for articles using keywords such as "Brain", "Growth", "Development", and "Breastfeeding", employing Boolean operators such as "AND", "OR", and "NOT." Results: Our search initially screened 15,412 studies, resulting in 600 articles. Eleven studies met our inclusion criteria and provided relevant information on the topic. Several studies have shown that exclusive breastfeeding and its duration are beneficial for neural development. Research suggests that breastfeeding improves brain architecture, white matter development, and cognitive performance. Additionally, studies indicate that the mother's intake of omega-3 fatty acids can enhance infant brain development, and specific micronutrients in breast milk, such as myo-inositol, may contribute to neural connectivity. Some findings also suggest that the child's sex may play a role in how breast milk benefits the brain. Furthermore, there is evidence of the strong influence of epigenetic compounds on the neurodevelopmental benefits of exclusive breastfeeding. Conclusions: This narrative review revealed findings that indicate breast milk has a positive impact on brain development. This emphasizes that breast milk has a positive impact on brain development. It underscores the importance of conducting additional research to understand how breastfeeding specifically influences neurodevelopment.